L-Ornithine and its Analogues as Inhibitors of Ornithine Decarboxylase: From Rational Drug to Specifically Devised Drugs - Mohamed Imran, P.K.; Subramani, K. (Asian Journal of Chemistry, 2011)
Difloromethyl ornithine (DFMO) is the first effective, rationally designed antiproliferative drug aimed at depleting polyamines from cells. Polyamines are considered critical regulators of cell growth, differentiation and cell death. The polyamine concentration is found increased in cancer cells. The diflouromethyl ornithine analogues may prove to be useful agents in the chemoprevention of cancer. These interact electrostatically and covalently with various macromolecules such as ornithine decarboxylase (ODC). Since the drug acts by electrostatic and covalent interactions a detailed study is made with various analogues of ornithine, including difloromethyl ornithine at the DFT and MP2 level of theory. The optimised parameters were used to compute reactivity parameters such as softness and electrophilicity index. The optimized geometry was used for docking with ornithine decarboxylase using genetic algorithm. The results are revealing as they help establish a drug with least toxicity in a quantitative approach unlike the rationally devised drug. The dockings interactions have been visualized and the interactions have been correlated with binding energy and electrophilicity concept.